2016
DOI: 10.1099/jmm.0.000191
|View full text |Cite
|
Sign up to set email alerts
|

Specific PCR, bacterial culture, serology and pharyngeal sampling to enhance the aetiological diagnosis of cellulitis

Abstract: It is often difficult to obtain a bacteriological diagnosis in patients with cellulitis. We examined the utility of molecular techniques and skin and throat cultures, as well as serology, in providing evidence of either Staphylococcus aureus or group A Streptococcus (GAS) presence in patients with cellulitis. Samples were collected from patients with a clinical diagnosis of cellulitis who were recruited into a prospective placebo-controlled clinical trial (C4C study, EudraCT 2013-001218-14). Specific PCR, pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The use of latex agglutination techniques and direct immunofluorescence on skin biopsy specimens increases the yield and has shown that β haemolytic streptococci, usually group A streptococci (GAS) or group G, represent the most prominent bacteria in studies of cellulitis and erysipelas, accounting for almost 80% of isolated organisms 45 Molecular testing6 and serology7 have been found to be of variable value but can improve the yield, especially if the patient has received antibiotics 8. It is probable that Staphylococcus aureus is not the causative agent in most cases where it was isolated, adopting an opportunistic bystander role.…”
Section: Introductionmentioning
confidence: 99%
“…The use of latex agglutination techniques and direct immunofluorescence on skin biopsy specimens increases the yield and has shown that β haemolytic streptococci, usually group A streptococci (GAS) or group G, represent the most prominent bacteria in studies of cellulitis and erysipelas, accounting for almost 80% of isolated organisms 45 Molecular testing6 and serology7 have been found to be of variable value but can improve the yield, especially if the patient has received antibiotics 8. It is probable that Staphylococcus aureus is not the causative agent in most cases where it was isolated, adopting an opportunistic bystander role.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Serological evidence for streptococcal infection with negative culture or PCR is conflicting. [ 25 , 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, serological evidence for a streptococcal etiology of cellulitis is conflicting. [ 25 , 26 ] In a planned larger study, we will add serological classification to the algorithm shown in Fig 1 , and this may result in some of the “indeterminate” lesions being classified as confirmed infected cases. For example, perhaps the rightmost controls in Fig 3 might have positive serological evidence of a streptococcal infection.…”
Section: Limitationsmentioning
confidence: 99%
“…11 It is probable that Staphylococcus aureus was not the causative agent in most cases where it was isolated, adopting an opportunistic bystander role. 10 This is supported by studies which demonstrate no extra benefit when adding an antibiotic active against met(h)icillin resistant S.aureus (MRSA) in the presence of MRSA carriage. 12 Four case-control studies focused on cellulitis of the leg.…”
mentioning
confidence: 99%
“…Classical testing with swabs or blood cultures only give a definite microbiological result in about 20 per cent of cases. 10 However, the use of latex agglutination techniques and direct immunofluorescence on skin biopsy specimens increases the yield and has clearly shown that beta-haemolytic streptococci (usually group A or group C/G) is found in almost 80% of isolated organisms. 11 It is probable that Staphylococcus aureus was not the causative agent in most cases where it was isolated, adopting an opportunistic bystander role.…”
mentioning
confidence: 99%